If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = 92 + -6x Reorder the terms: 10 + 3x = 92 + -6x Solving 10 + 3x = 92 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 10 + 3x + 6x = 92 + -6x + 6x Combine like terms: 3x + 6x = 9x 10 + 9x = 92 + -6x + 6x Combine like terms: -6x + 6x = 0 10 + 9x = 92 + 0 10 + 9x = 92 Add '-10' to each side of the equation. 10 + -10 + 9x = 92 + -10 Combine like terms: 10 + -10 = 0 0 + 9x = 92 + -10 9x = 92 + -10 Combine like terms: 92 + -10 = 82 9x = 82 Divide each side by '9'. x = 9.111111111 Simplifying x = 9.111111111
| 4x+x=300 | | 32x+12=50 | | 8b+4c=172/71 | | 16/8x+3=4/3 | | 33=11(c-6) | | (y+9)+y=10 | | 5x-15=15x-115 | | (x+9)+y=10 | | 7x-(5x-3)+6x=9 | | -15=13(4t-3) | | -(1)(p+17)=5(p-3) | | 3+2x=6x+7 | | 3+2x=4x+7 | | -1(p+17)=5(p-3) | | 3+2x=4x | | 8b+4c=172 | | -1(n-11)=-3 | | x+0.25x=3.75 | | 2.5x+3.7=11.5 | | y^2+5y=36/y^2+5y | | 0.5x-1.5=12.5 | | 8b+4c=171 | | (2x+2)/(1-x)^2=-1 | | (y^2)+(5y)=36/(y^2+5y) | | 7=6(x-4)-5 | | y^4+(10y^3)+(25y^2)=36 | | 4a-9whena=5 | | 31-7x=4 | | y+1/5=2 | | 80-4x=64 | | 3x+11=41 | | 9x-1=6x+26 |